2016
DOI: 10.1039/c5nj02059j
|View full text |Cite
|
Sign up to set email alerts
|

Structure–reactivity correlation in selective colorimetric detection of cyanide in solid, organic and aqueous phases using quinone based chemodosimeters

Abstract: The five new colorimetric chemodosimeters sense cyanide selectively and sensitively in aqueous and organic media via a nucleophilic addition mechanism exhibiting quantitative structure–reactivity correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The newly formed C-C bond involves one of the two DDQ carbon atoms bearing a cyano group as already observed when such addition occurred between DDQ and various nucleophilic carbon atoms of, for example, silyl enol ethers, 14 enaminones 15 or indoles. 16 If the C=O bond of the DDQ moiety adjacent to the quaternary carbon atom remains a double bond with a length of 1.203(8) Å, the formation of the zwitterion 11a is resulting from a proton transfer from the two starting components confirmed by the new C-OH single bond length of 1.334(8) Å. The crystal packing of the racemic 11a revealed that each enantiomer of 11a is interacting with the other one thanks to a π-π interaction producing a "tête-bêche" arrangement ( Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The newly formed C-C bond involves one of the two DDQ carbon atoms bearing a cyano group as already observed when such addition occurred between DDQ and various nucleophilic carbon atoms of, for example, silyl enol ethers, 14 enaminones 15 or indoles. 16 If the C=O bond of the DDQ moiety adjacent to the quaternary carbon atom remains a double bond with a length of 1.203(8) Å, the formation of the zwitterion 11a is resulting from a proton transfer from the two starting components confirmed by the new C-OH single bond length of 1.334(8) Å. The crystal packing of the racemic 11a revealed that each enantiomer of 11a is interacting with the other one thanks to a π-π interaction producing a "tête-bêche" arrangement ( Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…-3 )= 344 (25.0), 356 (25.9), 478 nm (1.4); HRMS (ESI-TOF): calcd. for C 16 4, 168.9, 155.0, 154.6, 143.4, 134.9, 115.6, 115.4, 106.3, 87.1, 82.5, 58.7, 47.0, 45.7…”
Section: Organic Synthesismentioning
confidence: 99%
“…Instead, meisoindigo 2a was formed in low yield (5–10%). When we carried out the reaction of 1a′ and DDQ (2.0 equiv) in the presence of TFA (20 mol%) in refluxing toluene for 18 h, the yield of 2a increased to 31%, as shown in Scheme . However, the reaction is less atom‐economic due to loss of valuable one molecule of indole.…”
Section: Methodsmentioning
confidence: 99%